Impact of NaCl reduction and substitution with KCl and CaCl2 on quality attributes of wheat-based bakery products - Musiienko, Daria; Jurkaninová, Lucie; Chrpová, Diana; Kourimská, Lenka (Frontiers in Nutrition, 2025)
Excessive sodium intake is a major contributor to hypertension and cardiovascular disease, prompting reformulation of commonly consumed foods such as bakery products. This study investigated the impact of reducing sodium chloride (NaCl) or partially replacing it with potassium chloride (KCl) and calcium chloride (CaCl2) on the sensory, rheological, and physical properties of wheat rolls and buns. Eight dough formulations with varied salt content and types were analyzed. Sensory profiling revealed that moderate NaCl reductions (14.4 g/1,000 g) preserved acceptability, while higher reductions or calcium-based substitutions introduced off-flavors such as bitterness and metallic aftertaste. Rheological tests showed that higher NaCl levels enhanced dough stability and consistency, whereas high CaCl2 levels decreased stability. Physical evaluation indicated that CaCl2 substitution led to higher product volume but also compromised dough cohesion. The findings support the feasibility of moderate sodium reduction and limited substitution in bakery products to improve public health outcomes without sacrificing product quality.